Regulation of T cell repertoires by commensal microbiota - Kim, Kwang Soon (Frontiers in Cellular and Infection Microbiology, 2022)
The gut microbiota plays an important role in regulating the host immune systems. It is well established that various commensal microbial species can induce the differentiation of CD4+ T helper subsets such as Foxp3+ regulatory T (Treg) cells and Th17 cells in antigen-dependent manner. The ability of certain microbial species to induce either Treg cells or Th17 cells is often linked to the altered susceptibility to certain immune disorders that are provoked by aberrant T cell response against self-antigens. These findings raise an important question as to how gut microbiota can regulate T cell repertoire and the activation of autoreactive T cells. This review will highlight microbiota-dependent regulation of thymic T cell development, maintenance of T cell repertoire in the secondary lymphoid tissues and the intestine, and microbiota-mediated modulation of autoreactive and tumor neoantigen-specific T cells in autoimmune diseases and tumors, respectively.